Memorandum of understanding between Universiti Teknologi MARA and Universitas Mulawarman / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2018)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.